Pattern of Bacteria, Antibiotic Uses and Sensitivity among Ear, Nose, and Throat Infectious Disease in Otolaryngology Ward in Tertiary Hospital - Yolla Sri Agustina (International Journal of Integrated Health Sciences, 2019)
Objective: To provide an overview of antibiotic use, bacterial patterns and sensitivity to antibiotics in the otolaryngology ward.